Microsynthetics in waters of the South American Pantanal - De Faria, Érika; Girard, Pierre; Gomes Camargo, Alan Lacerda; Moreschi Silva, Andressa Carla; Christo, Susete Wambier; Casado Coy, Nuria; Sanz-Lazaro, Carlos; Costa, Monica Ferreira (Frontiers in Environmental Science, 2022)
Microplastics are an emerging global threat to freshwater ecosystems. There is a growing number of microplastics studies in wetlands and floodplains such as the Pantanal. Microplastics in the Pantanal water courses, lakes, and floodplains were sampled with a plankton net in 16 locations in the Pantanal lowlands at varying distances from their potential urban sources over a two years period. Microplastics from the water samples were separated from sediments and organic matter and examined under stereomicroscope to identify and count microplastics. Visual determination was then confirmed by Raman spectrometry. The average±std microplastic concentration was 3.80±1.55 x/100L, ranging between 1.00 and 10.00 x/100L. Fibers, fragments, and films represented respectively 67.8%, 27.8%, and 4.4%, of the total microplastics. Surprisingly, synthetic blue fibers of non-identified composition, which Raman spectra suggest are composed of PbO, Cu2FeSn3S8, or LiNbO3, account for 51% of the 730 microplastics found. Other identified polymers include PP (18.2%), PET (16.9%), PVC (5.1%), PVA (4.4%), and LDPE (4.4%). The blue fiber, PP and PET were found at all sample locations. Microplastics concentrations varied from 2.25±0.47 x/100L to 4.75±1.52 x/100L across the sampling sites. Average concentrations varied in time from 3.40±1.13 to 4.33±1.81 x/100L. The median concentrations (1.3 x/100L) in lentic environments were significantly lower than in the lotic ones (1.7 x/100L). Urban human activities are a potential source of microplastics as the concentrations of these increased significantly with the population of nearest human agglomeration. These results indicate a widespread contamination of the Pantanal waters by microplastics. Furthermore, a microsynthetic of indeterminate composition possibly associated with e-waste is present everywhere in the Pantanal and more research is urgently needed to determine its composition and sources Contamination by micropolymers and other microsynthetics is likely to impact the Pantanal biota and eventually humans living in these floodplains.